Cache attack detection in virtualized environments. Issue 5 (4th July 2019) - Tank, Darshan; Aggarwal, Akshai; Chaubey, Nirbhay
Abstract: Cache Side Channel (CSC) attacks are prominent security threats in modern day processors. CSC attacks have caused a large impact in security and widespread concern in information security community. The objective of CSC attacks is to crack the confidentiality of a computer system and extract sensitive secrets through CPU caches. CSC attacks do not require any specific permission and just need access to a shared cache. CSC attacks are subtle, powerful and much more feasible in virtualized environments than in non-virtualized environments. To help protect security in virtualization environments, CSC attacks detection methods have become critical and important. The Flush+Flush cache attack technique, as the most recent CSC attack variant demonstrated that the state-of-the-art discovery methods can be simply sidestepped. In this paper, we introduce novel approach that make the detection of Flush+Flush cache attack in virtualized environments.